Social Media Content And Concept Of Mixtainment - Fahad Anis, Fahad Anis (2015)
The start of the 21 st century knew nothing about the revolution of communication and socialization that came in its first decade. The social media services like Twitter, Facebook, MySpace and many others proved a landmark in the world of communication, turning the whole globe into a global village. Yet, it is not clear to what extent these social media bring us the relevant information we seek. The researchers are interested to know the real content that these social media offer.